Australia’s China Question - Welch, Anthony (International Higher Education, 2019)
As in a number of other countries, Australian views on the Chinese influence in higher education and research have become a significant issue over the last year or more. The heavy dependence on the Chinese market by Australian universities is making university leaders nervous about a potential downturn in Chinese enrollments. Yet, no Confucius Institutes have been closed to date, and the concerns of national security agencies are universally accepted.